Evaluation of antihypertensive therapy through home blood pressure monitoring - Barochiner, Jessica; Alfie, José; Aparicio, Lucas; Morales, Margarita; Cuffaro, Paula E.; Rada, Marcelo; Galarza, Carlos; Ingaramo, Roberto; Resk, Jorge; Villamil, Alberto; Borrego, Carlos; Zilberman, Judith; et al. (Revista del Hospital Italiano de Buenos Aires, 2012)
Introduction: The cut-off value of 135/85 mmHg currently used to define hypertension diagnosis or inadequate blood pressure (BP) control by home blood pressure monitoring (HBPM) has been established by consensus and is continuously under debate. Objective: To determine HBPM role in the assessment of out-of-office BP control. Materials and methods: Patients older than 18 years, who were under treatment for hypertension performed a 24-hour, ambulatory blood pressure monitoring(ABPM) (Spacelabs 90207 validated device) followed by a HBPM (Omron 705 CP validated device). Subjects were divided into three groups, according to the BP level observed upon HBPM: Group 1: BP systolic (S) / BP diastolic (D); < 125/75 mmHg. Group 2: BP 125-134.9/75-84.9 mmHg. Group 3: BP ≥ 135 / ≥ 85 mmHg. Prevalence (%) of inadequate BP control by ABPM was compared among the three groups. Inadequate BP control was defined by day-time SBP > 135 or day-time DBP > 85 mmHg. Chi-square test was used to analyze differences in categorical data while the one way ANOVA test was used for continuous data.. A p value < 0.05 was considered statistically significant. Results: 108 treated hypertensive subjects were included in the study. Of them, 55.6 % were women, 46.3% had been diagnosed with dyslipidemia, 11.1% had diabetes and 7.4% had a history of cardiovascular or cerebro-vascular disease. Prevalence of inadequate BP control by ABPM was Group 1, 16.7%; Group 2, 29.3%; and Group 3, 62.2% (p < 0.001). Conclusions: Our findings suggest that the currently recommended cut-off value of 135/85 mmHg for HBPM underestimates a significant proportion of hypertensive patients with inadequate BP control if ABPM is used as the reference method. Larger studies with an appropriate design to determine a more accurate cut-off value should be performed
Keywords: : home blood pressure monitoring; ambulatory blood pressure monitoring; cut-off value